Studi Morfologi Serbuk Sari Enam Anggota Familia Rubiaceae - Zahrina Zahrina; Hasanuddin Hasanuddin; Wardiah Wardiah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2017)
AbstractThe aim of this study is to determine the pollen morphology of six species of familia Rubiaceae. The approach used in this study is a qualitative approach. This type of research is non-experimental by using descriptive method. Data was collected using acetolysis method. Data was analyzed descriptively. The results showed that the pollen unit of six species of familia Rubiaceae all have monad types. Shape of pollen can be divided into prolate spheroidal, subprolate, and prolate. Morinda citrifolia L. and Hedyotis corymbosa L.Lamk. included into prolate spheroidal. Ixora paludosa Kurz., Gardenia augusta Merr., Mussaenda frondosa L. included into subprolate. Coffea arabica L. included into prolate. The size of pollen can be divided into perminuta and minuta-. Hedyotis corymbosa L.Lamk., Coffea arabica L., and Ixora paludosa Kurz. included into perminuta. Morinda citrifolia L., Gardenia augusta Merr., and Mussaenda frondosa L. included into minuta-. Aperture type can be divided into inapertura, tricolporate, and monocolpate. Hedyotis corymbosa L.Lamk. included into inapertura. Coffea arabica L., Ixora paludosa Kurz., Morinda citrifolia L., Gardenia augusta Merr. included into tricolporate. Mussaenda frondosa L. included into monocolpate. Sculpture or exin ornamentation can be divided into scabrat type and reticulate type. Morinda citrifolia L. and Coffea arabica L. included into scabrat. Gardenia augusta Merr., Mussaenda frondosa L., Hedyotis corymbosa L.Lamk., and Ixora paludosa Kurz. included into reticulate. The conclusion of the study indicated that the pollen unit of six species of familia Rubiaceae have the same type, that is called as monad. The shape, size, aperture and sculpture of pollen is varies.Keywords: pollen, morphology, rubiaceae